2022
DOI: 10.3390/en15197271
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Resonance Tuning Technique for an Ultra-Broadband Piezoelectric Energy Harvester

Abstract: The main drawback of energy harvesting using the piezoelectric direct effect is that the maximum electric power is generated at the fundamental resonance frequency. This can clearly be observed in the size and dimensions of the components of any particular energy harvester. In this paper, we are investigating a new proposed energy harvesting device that employs the Automatic Resonance Tuning (ART) technique to enhance the energy harvesting mechanism. The proposed harvester is composed of a cantilever beam and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The optimization greatly reduces the number of attempts, efforts, and repetitions. Additionally, optimization increases output power 52 , 53 , 63 . The design parameters are the thickness of the base material (t), the length of the first beam ( ), the length of the second beam ( ), the length of the third beam ( ), the width of the first beam ( ), the width of the second beam ( ), the width of the third beam ( ),the height of the first tip mass ( , the height of the second tip mass ( and the height of the third tip mass ( .…”
Section: Finite Element Model and Analytical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization greatly reduces the number of attempts, efforts, and repetitions. Additionally, optimization increases output power 52 , 53 , 63 . The design parameters are the thickness of the base material (t), the length of the first beam ( ), the length of the second beam ( ), the length of the third beam ( ), the width of the first beam ( ), the width of the second beam ( ), the width of the third beam ( ),the height of the first tip mass ( , the height of the second tip mass ( and the height of the third tip mass ( .…”
Section: Finite Element Model and Analytical Analysismentioning
confidence: 99%
“…Zhao et al 51 suggested a graded metamaterial-based energy harvester with an emphasis on related vibrations (100 Hz) for broad-band and high-capability piezoelectric energy harvesting. Kouritem and Altabey 52 , 53 proposed the Automatic Resonance Tuning (ART) technique of two piezoelectric beams to manage the challenges of output power with a sharp peak, small enhancement in bandwidth, and large dimensions and weights of the harvesters. Therefore, a significant effort was made to extend the harvester's operating frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric Nanogenerators-Based Self-Powered Wearable Sensors: For the first time, an Au-MoSe2 composite ammonia (NH3) sensor was powered at room temperature, using a unique flexible piezoelectric nanogenerator (PENG) based on a two-dimensional (2D) semiconductor MoS2 flake, as shown in Figure 8 a. This design also showed a MoS2-based PENG device linked to a person’s body to gather various types of body motion energy, illustrated in Figure 8 b, demonstrating the device’s significant potential for usage in wearable electronics [ 124 , 125 , 126 , 127 , 128 ].…”
Section: Sensors Technology In Wearable Healthcarementioning
confidence: 99%
“…Bani-Hani et al (Bani-Hani et al 2022) designed a sensor of 17 harvesters to sense the vibrations resulting from an Earthquake excited in the frequency range (1-17 Hz). Kouritem et al (Kouritem et al 2022b;Kouritem and Altabey 2022;Altabey and Kouritem 2022) utilized the Automatic Resonance Technique for a cantilever of piezoelectric to produce wideband natural frequency. Erturk and Inman (Erturk and Inman 2009) investigated experimentally and analytically a bimorph with different connections (series and parallel).…”
Section: Introductionmentioning
confidence: 99%